Design and Develop Of A Web-Based E-Learning At SMP Humble Pensacola Christian School Jakarta North - Pambagyo, Agustinus Galih; Sudarsono, Bernadus Gunawan; Sharyanto, Sharyanto (Journal of Engineering, Technology and Computing (JETCom), 2025)
E-learning is teaching and learning that is supported and developed through technology and digital media, and is also a form of distance learning concept. Humble Pensacola Christian School is one of the educational institutions under the auspices of the ministry of religion engaged in education. Currently, the learning method at Humble Pensacola Christian School is still the same as other schools, namely by conducting learning between students and teachers in the classroom such as providing teaching materials, practicing questions, discussions, and giving school assignments. If the meeting between students and teachers does not occur, then the learning process cannot be carried out. This greatly impacts the lack of student understanding of the subject matter. The methods used in this research are observation, interview, literature study, design and testing methods. Then in this research there is also system modeling with UML (Unifield Modeling Language) method as well as PHP as a programming language and Mysql as a DBMS used for the development of “Web-based E-Learning at Humble Pensacola Christian School North Jakarta”.